2016
DOI: 10.1111/1462-2920.13523
|View full text |Cite
|
Sign up to set email alerts
|

Oligotrophic lagoons of the South Pacific Ocean are home to a surprising number of novel eukaryotic microorganisms

Abstract: The diversity of microbial eukaryotes was surveyed by environmental sequencing from tropical lagoon sites of the South Pacific, collected through the American Museum of Natural History (AMNH)'s Explore21 expedition to the Solomon Islands in September 2013. The sampled lagoons presented low nutrient concentrations typical of oligotrophic waters, but contained levels of chlorophyll a, a proxy for phytoplankton biomass, characteristic of meso- to eutrophic waters. Two 18S rDNA hypervariable sites, the V4 and V8-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…Especially over the last 10 years, molecular methodologies have allowed for the characterization of these groups at the taxon or species level, revealing enormous diversity across all trophic levels of marine microbial communities and identifying numerous ecotypes occupying distinct ecological niches (Carlson et al, 2007;Venter et al, 2004). More recently, environmental sequencing has revealed a surprising diversity of small-sized PPE and new eukaryotic lineages continue to be discovered and characterized (Kashtan et al, 2014;Kim et al, 2016;Lepère et al, 2009;Rii et al, 2016a), while also revealing the importance of viruses in regulating phytoplankton communities (Brum et al, 2015;Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Especially over the last 10 years, molecular methodologies have allowed for the characterization of these groups at the taxon or species level, revealing enormous diversity across all trophic levels of marine microbial communities and identifying numerous ecotypes occupying distinct ecological niches (Carlson et al, 2007;Venter et al, 2004). More recently, environmental sequencing has revealed a surprising diversity of small-sized PPE and new eukaryotic lineages continue to be discovered and characterized (Kashtan et al, 2014;Kim et al, 2016;Lepère et al, 2009;Rii et al, 2016a), while also revealing the importance of viruses in regulating phytoplankton communities (Brum et al, 2015;Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, environmental sequencing has revealed a surprising diversity of small sized picophytoeukaryotes (PPE) and new eukaryotic lineages continue to be discovered and characterized (Kashtan et al, 2014;Kim et al, 2016;Lepère et al, 2009;Rii et al, 2016b) while also revealing the importance of viruses in regulating phytoplankton communities (Brum et al, 2015;Huang et al, 2015).…”
mentioning
confidence: 99%
“…Purification was done following the manufacturer instructions. PCR amplification of either the V4 or V8-9 regions of 18S rDNA were performed as previously described (Kim et al, 2016). Both V4 and V8-9 regions of the 18S rRNA gene were sequenced because of their extensive use for eukaryotic diversity (Nickrent and Sargent, 1991;Amaral-Zettler et al, 2009;Massana et al, 2015) and to compensate the existing primer bias of each region.…”
Section: Dna Extraction and Next-generation Sequencingmentioning
confidence: 99%
“…Both V4 and V8-9 regions of the 18S rRNA gene were sequenced because of their extensive use for eukaryotic diversity (Nickrent and Sargent, 1991;Amaral-Zettler et al, 2009;Massana et al, 2015) and to compensate the existing primer bias of each region. Amplicon libraries were prepared as in Kim et al (2016) (further details about library preparation can be found in Supplementary Table). Sequencing was performed on Illumina MiSeq platform (2 × 300 bp) at the Cornell University Sequencing Core (New York; USA).…”
Section: Dna Extraction and Next-generation Sequencingmentioning
confidence: 99%
See 1 more Smart Citation